IMPROVING DIGITAL PLATFORM AS TOURISM DEVELOPMENT: A ECONOMIC BENEFICIAL FOR UMBUL PONGGOK COMMUNITY, KLATEN, CENTRAL JAVA - Mochamad Kevin Romadhona; Irma Wati; Nabila Rizky Maulida; Sri Endah Kinasih (Jurnal Pendidikan Sosiologi Undiksha, 2022)
Klaten’s is the part Region in Central Java which has natural potential. One of the most popular village in Klaten is Umbul Ponggok. The Ponggok’s village well known as the Natural Sources which consist of beautiful places. The Ponggok Village have several umbul but the most popular umbul is Umbul Ponggok, located in Polanharjo, Klaten, Central Java. In the past, Umbul Ponggok was used a bathing place for community and still not populer. Now, Umbul Ponggok is a popular place because management and using technology. The using of technology can be branding of Ponggok’s Village as a tourism village, it has resulted increasing village income. The increase has made Ponggok’s Village more empowered economically and resulted change as social transformation. The success of Umbul Ponggok’s in utilizing technology as a tourism village branding increasing interest community to explore many activities. Umbul Ponggok offering underwater activities such as snorkeling, diving,a and underwater photography. The purpose of this research to describe about social transformation community in Pongok’s village, Klaten, Central Java. This research using qualitative method and indepth interview as the technique data collecting. This result to describe about social transformation community Ponggok’s village of post transform to tourism village.